Growing greener cities : urban sustainability in the twenty-first century - Wachter, Susan M.; Birch, Eugenie Ladner (City in the twenty-first century book series., 2008)
This thoroughly illustrated collection of essays, written by scholars as well as practitioners of urban policy, gives a panoramic view of sustainability and environmental issues for green-minded city planners, policy makers, researchers, and citizens.